Evaluation of the Level of Sirtuin7 and Some Biochemical Parameters in Patients with Cardiovascular Disease (المجلة الدولية للبحوث العلمية, 2024)
The regulatory protein SIR7 Homolog 7 is known as sirtuin7 and is one of the seven most important sirtuins found in mammals, it is located primarily in the nucleus and is released from the nucleus into the nucleoplasm in response to stress. This study evaluated the relationship between low levels of sirtuin7 in the blood and cardiovascular disease in addition to studying the effect of gender on the level of sirtuin7 and the measured biochemical variables. Blood samples were collected from 45 patients with cardiovascular disease and 45 blood from healthy people as a control group. The following Clinical examinations was performed for both cardiovascular patients and control group: Sirtuin7 enzyme (SIRT7), tumour necrosis factor alpha (TNF-α), lipoxygenase enzyme (LOX), superoxide dismutase (SOD), albumin, glutathione peroxidase (GPx), glutathione (GSH) and malondialdehyde (MDA), in addition to studying the effect of sex on all of these examinations. Recorded results that low levels of the enzyme sirtuin7 in blood serum (2.6885 ± .88859) occurred in patients with cardiovascular disease compared to control group (13.5435 ± 2.19009). A significant difference was recorded at the probability level (p ≤ 0.01) in the levels of Sittuin7, tumour necrosis factor-α, lipoxygenase enzyme, lipoxygenase enzyme, superoxide dismutase.